Life Skills Is One of the Alternative New Models in the World of Education to Form Superior Human Resources - mulyani, sri rochani; kadarisman, sumeidi; ahmaddien, iskandar (2020)
This study aims to determine the effect of the dimensions of life skills to form superior student. The data used are primary data by distributing questionnaires to 299 respondents. The methodology used is structural equational modeling of second order with Amos 23 as software. The results of this study indicate that the dimensions of life skills are subject to making superior student. The contribution of this research is that the curriculum given to students in the future must include elements of life skills. The renewal in this study is that even though life skills are not new, there are still very few studies on this subject, especially for students.